2017
DOI: 10.1016/j.neubiorev.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Memory scrutinized through electrical brain stimulation: A review of 80 years of experiential phenomena

Abstract: Electrical brain stimulations (EBS) sometimes induce reminiscences, but it is largely unknown what type of memories they can trigger. We reviewed 80 years of literature on reminiscences induced by EBS and added our own database. We classified them according to modern conceptions of memory. We observed a surprisingly large variety of reminiscences covering all aspects of declarative memory. However, most were poorly detailed and only a few were episodic. This result does not support theories of a highly stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 92 publications
3
71
0
Order By: Relevance
“…Recollection is also associated with a parietal positive event-related potential, which is dependent on HC integrity (Smith and Halgren, 1989), and correlated across trials with pHC and retrosplenial BOLD activation (Hoppstädter et al, 2015). HC stimulation can induce intense feelings that current experience is being re-lived (déjà vu) as well as vivid recollections of previous experiences (Halgren et al, 1978;Curot et al, 2017). These considerations raise the possibility that pHC-SSR are more prominent in humans because they help support autobiographical memory; further investigations with behavioral assessments are necessary to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recollection is also associated with a parietal positive event-related potential, which is dependent on HC integrity (Smith and Halgren, 1989), and correlated across trials with pHC and retrosplenial BOLD activation (Hoppstädter et al, 2015). HC stimulation can induce intense feelings that current experience is being re-lived (déjà vu) as well as vivid recollections of previous experiences (Halgren et al, 1978;Curot et al, 2017). These considerations raise the possibility that pHC-SSR are more prominent in humans because they help support autobiographical memory; further investigations with behavioral assessments are necessary to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Second, intracranial electrophysiology in humans has shown that the spontaneous recall of episodic memories is immediately preceded by elevated firing rates (more action potentials) in single neurons in the MTL, but not elsewhere [40]. And when electrically stimulating the brain with intracranial electrodes, the only area that has reliably been shown to elicit experiences resembling mind-wandering -memories, complex visual imagery, and dream-like experience -is the MTL [15,33,41].…”
Section: A Dual-process Model Of Mind-wandering: Generation and Evalumentioning
confidence: 99%
“…Various psychic symptoms, also known as “experiential phenomena” [ 1 ], reflect altered contents of consciousness during partial seizures [ 2 ]. These include a wide range of déjà-experiences [ 3 ], which phenomenology and content-wise vary from déjà-vu (a transitory mental state whereby a novel experience feels as if it is familiar) to reminiscence (the involuntary recall of memories, either semantic or episodic) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…We aimed to clarify its definition, its phenomenology and its content. As other subtypes of déjà-experiences relate to specific anatomical substrates [ 4 , 15 , 23 , 24 ], we hypothesized that déjà-rêvé could be induced by specific EBS locations. Finding clues about the neural correlates of déjà-rêvé could help clinicians focus on specific brain areas in epileptic patients and could increase our knowledge about the neural correlate of dreams.…”
Section: Introductionmentioning
confidence: 99%